The Aspects of Mandibular Movements in Swallowing - Ohara, Hisakazu (Nihon Hotetsu Shika Gakkai Zasshi, 1975)
The aspects of swallowing movements, habitual: opening and closing movements and rest position were investigated from functional points of view. Three dimentional measuring apparatus of the mandibular movements at the incisiorinferius combined with optical-fiber, motion-analyzer and electric-computer was used in coordination with teeth contacts apparatus with accelerometer and swallowing meter. The following conclusion is obtained based on the experimental result. 1) The clinical mandibular rest position moves within about 1.5mm to anterior and posterior direction, about 1.4 mm to upper and lower direction, and about 1.0mm to right and left direction. 2) In habitual opening and closing movements, the opening path is positioned in front of the closing path. Habitual opening and closing movements tend to be in a left and anterior position from the rest position. 3) Intercuspal position has a narrow range within about 0.4 mm to anterior and posterior direction and to upper and lower direction and within about 0.3 mm to right and left direction. 4) Tooth contact is recognized in empty swallowing with sitting and lying postures and in swallowing after mastication. 5) Mandibular movement in swallowing is complicated. Ingeneral, it moves from posterior to anterior in empty swallowing. But it does not indicate a definite direction in swallowing after mastication in comparison with empty swallowing. 6) Mandibular in swallowing is held in a range of 0.9mm and the range of slidingis within 0.5mm before and after the fixation. 7) Swallowing movement in lying posture is slow and powerful, and in swallowing after mastication, tooth contact is strong than in sitting posture.